PENGEMBANGAN MEDIA PRAKTIKUM MATERI PERTUMBUHAN DAN PERKEMBANGAN MENGGUNAKAN HIDROPONIK RAKIT APUNG DAN RASIO NUTRISI - Gunawan, David Indra; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to determine the effect of floating raft hydroponic media products on static and dynamic methods and different nutrient ratios as media in growth practicum activities in schools. The method used was research and development (R & D) method using 6 stages, starting from potential and problems, data collection, product design, design validation, design revisions and limited trials. Stage The trial involved students and validators as material and media experts. The research instruments were in the form of validation questionnaires, student response questionnaires and student practical worksheets. The results of the prototype validation and floating raft hydroponic media products by material and media experts included the feasible category (100%). Based on the results of the questionnaire responses of students showed that students strongly agreed that the floating hydroponic raft was used as laboratory work (86.80%) Kata kunci : floating raft hydrophonics, laboratory work media, student responses